The Combination of Shading and Potassium Application Regulated the Bulb Active Ingredients Accumulation in Fritillaria thunbergii Miq. by Affecting Rhizosphere Microecology - Leran Wang; Bingbing Liang; Jia Liu; Huizhen Jin; Zixuan Zhu; Siyu Hao; Shumin Wang; Xiaoxiao Sheng; Xinshu Zhou; Honghai Zhu; Ning Sui (Microorganisms)
The bulbs of the lily plant Fritillaria thunbergii Miq. possess substantial medicinal properties for relieving coughs and clearing the lungs. However, excessive pursuit of yield during cultivation has led to a decrease in medicinal ingredients. Therefore, we aimed to investigate the effects of two single-factor treatments, shading (SK0) and potassium application (S0K), and their coupling treatment (SK) on bulb biomass and medicinal substance content, along with the role of rhizosphere microorganisms. Shading increased the content of active ingredients in bulbs by approximately 11.7% while decreasing bulb biomass by approximately 11.3%. SK treatment mitigated the biomass reduction caused by SK0 treatment while enhancing the accumulation of active ingredients in F. thunbergii, up to 1.2 times higher than that of SK0 treatment. In rhizosphere soil, Allorhizobium–Neorhizobium–Pararhizobium–Rhizobium (ANPR), Chryseobacterium, Brevundimonas, and Phoma exhibited significant positive correlations with medicinal components, among which ANPR, Brevundimonas, Chryseobacterium, and Phoma were responsive to SK treatments. Also, Burkholderia–Caballeronia–Paraburkholderia (BCP) and Brevundimonas responded to changes at different growth stages of F. thunbergii. The relative abundance of these microorganisms was associated with the alterations of soil factors resulting from shading or K application. Our results indicate that these microorganisms are beneficial to the growth of bulbs and the synthesis of active components in F. thunbergii. The combination of shading and K application may regulate the accumulation of medicinal substances in F. thunbergii by modulating the structure of the soil microbial community. Our results serve as a reference for soil improvement for medicinal plant cultivation.